Seismic Hazard Assessment of Northern Iraq - Aleqabi, Ghassan I.; Ghalib, Hafidh A. A. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Seismic hazard assessment is the estimation of the likelihood that an earthquake will occur in a given geographic area, within a particular window of time, and that it develops ground motion acceleration or intensity at a specific place within a specific area that exceeds a given threshold. It can be used as a tool for rational planning and designing in seismically active areas. For seismic hazard quantification, statistical analyzes of earthquake catalogs of northern Iraq and surrounding regions are carried out to estimate the rate and spatial distribution of earthquake events as a function of the magnitude and geographical location. Most techniques for estimating the likelihood of occurrence within a particular area are based on historical data of that region. An essential step in characterizing seismic hazards in an area is to determine the frequency and location of past earthquakes. Earthquakes tend to cluster around the most active faults. Kernel density estimators using a Gaussian kernel are applied to assess seismic hazard in the area. We performed Probabilistic Seismic Hazard Analysis (PSHA) to quantify the probability of exceeding a given ground motion in the area. The highest probability of seismic hazard exists in the northeastern part of Iraq and the Zagros regions. The seismic hazard is lowest to the west and south of northern Iraq, in the Mesopotamian valley. The comparison between the obtained results and the seismotectonic models of Iraq reveals that the current distribution of regional earthquakes agrees with the seismotectonic provinces of Iraq.
Keywords: SeismicHazardriskprobabilityPSHA